Public private partnership building along the seed value chain to support nature positive seed system development - Niane, Abdoul Aziz; Agrawal, Shiv Kumar; Bishaw, Zewdie; Kemal, Seid Ahmed (2023)
Partners in Kenya and India along the seed value chain have been engaged for partnership building on seed system development for Nature Positive Solutions.